О.A. Verigo scientific activity in the fild of microbiology in the University of Odesa (Novorosiy sky University )(1837–1905) - В. О. Кузнєцов (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2010)
The article is devoted to the 105th anniversary from the death date (13.03.1905) of a prominent scientist, the honoured professor О.A. Verigo (05.12.1837–26.03.1905). The main events of О.A.Verigo’s scientific activity in the field of microbiology and biological technologies were studied on the basis of the archive materials of the State Odesa Region Archive, on the scientific archive of the Archive Studying Institution NLU named after V.I. Vernadsky of the Ukrainian Academy of Sciences and other literature sources.